Students’ perspectives on bilingualism in Indonesian EFL classroom: A case study on teachers' L1 use as one of EMI - Noviyati, Dewi; Suwandi, Suwandi; Senowarsito, Senowarsito (Universitas PGRI Semarang, 2023)
In today’s interconnected world, where global communication is more accessible than ever, English has emerged as the dominant lingua franca. As a result, bilingual and multilingual speakers of English are increasingly common. Within the Indonesian EFL (English as a Foreign Language) context, bilingualism—often extending to multilingualism—has become a prevalent phenomenon, particularly due to the predominance of non-native English-speaking teachers who share the same first language (L1) as their students. This situation has led to the proposal of a